The Impact of Paid Parental Leave on Labour Supply and Employment Outcomes - Barbara Broadway; Guyonne Kalb; Duncan McVicar; Bill Martin (Institute for the Study of Labor (IZA), 2016)
The introduction of the Australian Paid Parental Leave scheme in 2011 provides a rare opportunity to estimate the labour supply and employment impacts of publicly-funded paid leave on mothers in the first year post-partum. The almost universal coverage of the scheme coupled with detailed survey data collected specifically for this purpose means that eligibility for paid leave under the scheme can be plausibly taken as exogenous following a standard propensity score matching exercise. In line with much of the existing literature, we find a positive impact on leave taking in the first half year and on the probability of eventually returning to work in the first year. The paper provides new evidence of a positive impact on continuing in the same job and under the same conditions. Further new evidence shows that disadvantaged mothers – low income, less educated, without access to employer-funded leave – respond most to the scheme.
Keywords: J13; J18; J22; 330; labour supply; parental leave; mothers; duration analysis; propensity score matching